Using birds as indicators of Neanderthal environmental quality: Gibraltar and Zafarraya compared. (9th November 2016) - Finlayson, Clive; Finlayson, Stewart; Giles Guzman, Francisco; Sánchez Marco, Antonio; Finlayson, Geraldine; Jennings, Richard; Giles Pacheco, Francisco; Rodriguez Vidal, Joaquin
Abstract: We compare the Middle Palaeolithic sites of Gibraltar and Zafarraya in southern Iberia. We use birds as indicators of environmental quality and demonstrate huge differences between coastal and inland, mountain, sites separated by less than 150 km. We conclude that the Gibraltar sites represented locations of repeated occupation by Neanderthals over tens of millennia whereas Zafarraya represents a site of sporadic visits for particular prey. This is in response to very different climatic conditions. Our results show how important ecological quality is in understanding Palaeolithic sites and metapopulations and how birds are particularly informative in our understanding of the ecology of such sites.